THE HUMAN PRESSURE IN THE APUSENI NATURAL PARK - Claudiu FILIMON; Grigore Vasile HERMAN; Luminița FILIMON; Stelian NISTOR; Mariana Laura HERMAN; Liviu BUCUR (Revista Română de Geografie Politică)
The present study captures the pressure exerted by the population on the Apuseni Natural Park (ANP), from the perspective of the significant role of the human component in the conservation and development of these fragile areas from a natural and human point of view. The proposed study is focused both on the quantitative characteristics (general density, physiological density, pasture load) and on the quantitative ones (naturality index, human pressure through forestry), analyzed at the level of the ANP. The analysis of these indicators highlights the fact that, from the point of view of the human pressures exerted at the level of the ANP, it is not a strong one, and moreover it can jeopardize the optimal use of the potential of the ANP.